DOES FINANCIAL STATEMENT FRAUD MODERATE THE INFLUENCE OF CREDIT RISK AND CAPITAL ADEQUACY ON FINANCIAL DISTRESS - Fadillah, Haqi; Aryati, Titik (Universitas Pakuan, 2025)
ABSTRACTIn Indonesia's banking sector, altering or tampering with financial statements is a common practice aimed at portraying better company performance. Nevertheless, this behavior often signals underlying financial struggles or distress within the banks. This study evaluates whether Financial Statement Fraud moderates the linkage between Credit Risk, Capital Adequacy, and Financial Distress. The observation includes banking entities listed on the Indonesia Stock Exchange within the 2019 to 2023 period. Hypotheses were examined using Moderated Regression Analysis (MRA). Empirical evidence reveals that elevated Credit Risk significantly elevates the probability of Financial Distress in banks. Conversely, robust Capital Adequacy serves as a primary safeguard to maintain the fiscal stability of the firm. Financial Statement Fraud proves to exacerbate the detrimental impact of asset risks, obscuring financial distortion signals for investors. These revelations underscore the urgency of reporting integrity and strict compliance with government regulations to prevent insolvency. Maintaining high transparency in financial statements is essential for mitigating future Financial Distress risks.ABSTRAKDi sektor perbankan Indonesia, pengubahan atau pemalsuan laporan keuangan sudah menjadi praktik yang umum dilakukan dengan tujuan untuk menunjukkan kinerja perusahaan yang lebih baik. Namun, kenyataannya, tindakan ini sering kali menandakan adanya permasalahan keuangan atau financial distress yang dialami oleh bank. Penelitian ini menganalisis peran Financial Statement Fraud dalam memoderasi keterkaitan antara Credit Risk, Capital Adequacy, dan Financial Distress. Data observasi mencakup entitas perbankan di Bursa Efek Indonesia dengan rentang waktu pengamatan dari tahun 2019 hingga 2023. Pengujian hipotesis dilakukan menggunakan metode Moderated Regression Analysis (MRA). Bukti empiris mengungkap bahwa peningkatan Credit Risk secara signifikan mempercepat kondisi Financial Distress pada sektor perbankan. Sebaliknya, penguatan Capital Adequacy terbukti memberikan proteksi terhadap potensi kegagalan keuangan yang mungkin dialami perusahaan. Temuan menunjukkan bahwa Financial Statement Fraud memperparah dampak buruk risiko aset terhadap stabilitas ekonomi perbankan. Optimalisasi tata kelola tersebut krusial guna memitigasi potensi Financial Distress pada institusi perbankan di masa depan